Implementation of Fuzzy Logic Mamdani in Determining Employee Job Appraisal of PT Exclusive Panca Anugerah Using Matlab - Lutfi Aziz Febrika Ardy; Aqim Try Kurnia; Keinanjung Ruswandi; Muhammad Al-Ghifari; Muhamad Zikri Abdillah; Vina Puspitasari; Muhammad Danang Mukti Darmawan; Nanda Octavia; Sesar Husen Santosa (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Human resources are one of the important components of a company. With good employee performance, it can be interpreted that the system in the company is also running well. This method utilizes attendance and performance variables to assess the employee. This journal aims to see and monitor how an employee's performance in a company is working optimally or not. It uses the implementation of fuzzy logic Mamdani as a proof model, coupled with the Matlab application toolbox that allows evaluation and assessment of performance according to the existing scenario. The results of this experiment show the effectiveness of providing accurate scores and can also help management to make more informed decisions